Adapted Education for Gifted Students in Norway: A Mixed Methods Study - Astrid Lenvik; Lise Øen Jones; Elisabeth Hesjedal (MDPI AG, 2023)
In this article, we describe the mixed methods research (i.e., quantitative survey and qualitative interviews) we conducted to investigate adapted education for gifted students in Norway. The survey results showed that the teachers (n = 132) used differentiation strategies and agreed that gifted students need an adapted education that extends beyond the regular curriculum. We identified three themes related to adapted education based on an analysis of the student interview data (n = 17, aged 12-15) and four themes based on an analysis of the teachers' responses to the open-ended survey question regarding adapted education. We also investigated similarities and differences between teacher and student themes: both groups reported similar enrichment strategies applied within adapted education and similar barriers and systematic challenges to its facilitation.